The Effects of Ginger, Diazepam and Metoclopramide in Patients Receiving Dental Treatment - Fayhaa AM Al - Mashhadane; Mohammad A Mohi-Al Deen (University of Mosul, College of Dentistry, 2010)
Aims: To diagnose and treat patients with gagging reflex during dental treatment and to compare ef-fects of ginger, diazepam and metoclopramide as different treatment modalities. Materials and Me-thods: This study was carried out on 120 dental patients, 37 males and 83 females who they are suffer-ing from moderate to severe gag reflex, their ages was ranged between 31 - 68 years old. The sample is randomly subdivided into 4 groups, each group consist of 30 patients, they was received different treatments (ginger, diazepam, metoclopramide and glucose (placebo)). Severity of gag reflex before and after treatments is reported depending on patient's words and direct reaction. Results: Kruskal - Wallis test was used to compare the response to treatment in 4 groups and there was significant differ-ences between them (p≤ 0.00). Conclusion: Ginger is effective antiemetic agent and can be useful for reducing nausea and vomiting (gag reflex) during and after dental treatment.